Improving Quantitative Abilities and Attitudes in Clinical Psychology Courses: Longitudinal Assessment of a Blended Learning Intervention. (October 2021) - Sockol, Laura E.; Ellison, William D.; Stutts, Lauren A.; Knouse, Laura E.
Background: Many students report negative attitudes toward research methods and statistics (RMS), and these attitudes are associated with impaired performance. Student interest in clinical psychology suggests that clinical courses may provide a promising venue for integrating RMS instruction. This approach may be particularly valuable for students from underrepresented groups in psychology. Objective: We evaluated whether integrating core RMS concepts into undergraduate clinical psychology courses using a blended learning intervention improved students' quantitative knowledge and attitudes. Exploratory analyses assessed whether the intervention had differential efficacy for students from underrepresented groups. Method: Students completed pre- and post-course assessments of content knowledge, perceived RMS competence, implicit theories of quantitative skills, and statistics anxiety. We compared changes in student outcomes before ( n = 101) and after ( n = 91) implementing the blended learning intervention. Results: Overall, the intervention did not result in greater improvements in content knowledge, perceived RMS competence, or statistics anxiety. However, exploratory analyses suggested that the intervention was more effective for first-generation and racial/ethnic minority students. Change in endorsement of a growth-oriented mindset for quantitative skills was marginally stronger among students in courses implementing the blended learning intervention. Conclusion: These findings suggest that integrating RMS content in clinical psychology courses may confer modest benefits for students' knowledge and attitudes toward quantitative skills, especially among students from underrepresented groups.